Anatomical investigations on endemic Campanula romanica Savul. and their ecological significance - Gostin, Irina; Oprea, Adrian (Bangladesh Journal of Botany, 2013)
Histo-anatomical properties of the vegetative organs in endemic Campanula romanica Savul. were presented. The structure of the root, rhizome, stem and leaves (basal and caulinar) was analysed with emphasis to the adaptation of this rare species to the environmental conditions. Moderate xeric features were observed at the anatomical level, despite the dry living area. These are correlated with the species life conditions and life cycle. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15877 Bangladesh J. Bot. 42(1): 139-144, 2013 (June)